Active RF pulse compression using electrically controlled semiconductor switches - Jiquan Guo; Tantawi, S. (2007 IEEE Particle Accelerator Conference (PAC), 2007)
In this paper, we will present our recent results on the research of the ultra-fast high power RF switches based on silicon. We have developed a switch module at X-band which can use a silicon window as the switch. The switching is realized by generation of carriers in the bulk silicon. The carriers can be generated electrically or/and optically. The electrically controlled switches use PIN diodes to inject carrier. We have built the PIN diode switches at X-band, with <300 ns switching time. The optically controlled switches use powerful lasers to excite carriers. By combining the laser excitation and electrical carrier generation, significant reduction in the required power of both the laser and the electrical driver is expected. High power test is under going.